Effects of epidurally administered dexmedetomidine and dexamethasone on postoperative pain, analgesic requirements, inflammation, and oxidative stress in thoracic surgery - Peršec Jasminka; Šribar Andrej; Ilić Monika; Mamić Ivan; Kifer Domagoj; Domijan Ana-Marija; Maleš Željan; Turčić Petra (Acta Pharmaceutica)
The aim of this study was to compare the effects of dexmedetomidine and dexamethasone as adjuvants to preoperative epidural administration of local anesthetic (ropivacaine) in thoracic surgery on the postoperative level of pain, use of analgesics, inflammation, and oxidative stress. The study enrolled 42 patients who underwent elective thoracic surgery in a one-year period at the University Hospital Dubrava (Zagreb, Croatia). Based on a computer-generated randomization list the patients were assigned to the dexmedetomidine (n = 18) or dexamethasone (n = 24) group. Postoperatively, patients of dexmedetomidine group reported lower pain (VAS value 1 h post surgery, 3.4 ± 2.7 vs. 5.4 ± 1.8, dexmedetomidine vs. dexamethasone, p < 0.01) and had lower anal-gesic requirements in comparison with dexamethasone group. Thus, dexmedetomidine in comparison with dexamethasone was more efficient in lowering pain and analgesia requirements 24 h after the surgery. On the contrary, dexamethasone had better anti-inflammatory properties (CRP level 24 h post surgery, 131.9 ± 90.7 vs. 26.0 ± 55.2 mg L−1, dexmedetomidine vs. dexamethasone, p < 0.01). Both dexmedetomidine and dexamethasone exhibited antioxidant effects, however, their antioxidant properties should be further explored. The results of this study improve current knowledge of pain control in thoracic surgery.